Design and simulation of a lithium-ion battery at large C-rates and varying boundary conditions through heat flux distributions. (February 2018) - Panchal, S.; Dincer, I.; Agelin-Chaab, M.; Fraser, R.; Fowler, M.
Highlights: Designed and developed battery cooling system. Studied average and peak heat flux distributions. Developed and validated battery thermal model using neural network approach. Validation of heat flux at different discharge rates and BCs. Validation of voltage distributions at different discharge rates and BCs. Abstract: In this paper, the heat flux distributions on a prismatic lithium-ion battery at 1C, 2C, 3C and 4C discharge rates under various operating temperatures and boundary conditions (BCs) of 22 °C for air cooling and 5 °C, 15 °C, and 25 °C for water cooling are presented. The goal is to provide significant quantitative data on the thermal behaviour of lithium-ion batteries. In this regard, a battery thermal management system with water cooling is designed and developed for a 20 Ah capacity pouch type lithium-ion battery using dual cold plates. Three heat flux sensors are placed at different locations on the principle surface of the battery: the first near the anode, the second near the cathode, and the third at the mid surface of the body. From these the average and peak heat flux values are obtained and presented in this study. In addition to this, the heat flux and voltage distributions are simulated using the neural network approach with the above mentioned discharge rates and BCs. The present results show that increased discharge rates and decreased operating temperature result in increased heat fluxes at the three locations as experimentally measured. Furthermore, the sensors nearest the electrodes (anode and cathode) measured the heat fluxes (and hence temperatures) higher than the sensors located at the center of the battery surface.